PENYULUHAN RUMAH SEHAT IDAMAN SETIAP ORANG - Reni Raafidiani; Ade Yuliana; Tri Pratiwi Olivia Riska Bokings (PUAN INDONESIA, 2023)
Home is a place where we must feel safe and comfortable, this is of course an important foundation for our role as residents of the house. But human awareness is still lacking in creating a safe and comfortable home. Sometimes humans take trivial things about house ventilation, sanitation of temporary toilet and lighting of a room. The important thing is to have place to live they did not conciderate about healty place. The purpose of community service is to provide counseling about a healthy home which is everyone's dream in Taman Bukit Cibogo, RT.08/RW.17, Kelurahan Leuwigajah, Kecamatan Cimahi Selatan, Kota Cimahi. In order to acive the desire out come, sosialisation is required about healty house. A healthy home doesn't have to be luxurious, but a healthy home is a comfortable place for its residents, so apart from being physically healthy, you also have to pay attention to it physiologically. The results of this dedication service participants know the conditions for a healthy house and healty soul apart from that the service participants can apply it to their respective homes.